Differential expression of VEGF-Axxx isoforms is critical for development of pulmonary fibrosis - Barratt, Shaney L.; Blythe, Thomas; Jarrett, Caroline; Ourradi, Khadija; Shelley-Fraser, Golda; Day, Michael J.; Qiu, Yan; Harper, Steve; Maher, Toby M.; Oltean, Sebastian; Hames, Thomas J.; Scotton, Chris J.; et al. (American Thoracic Society, 2017)
RATIONALE